(untitled) (E Global Congress, 2024)
The topic of our research is one of the most relevant, because the use of information and communication technologies in the formation of lexical competence among school students contributes to a stronger and faster assimilation of lexical material and involuntary memorization of language units. At the present stage of development of the methodology of teaching foreign languages, one of the most important problems is the problem of the formation of lexical competence, which is solved in the course of communicative actions performed by students.